Current scenario of livestock development and potential interventions for livelihood improvement: Case of Jharkhand, India - Sirohi, S.; Chauhan, A.K. (International Livestock Research Institute, 2011)
This background paper identifies the poor communities engaged in livestock husbandry in Jharkhand, problems faced by them and scope for growth of this sector. The performance of the livestock sector has not been optimum due to lack of critical inputs and services and poor linkage with the market. As the farmers do not adopt improved breeding, feeding and management practices, the productivity of large and small ruminants is poor. Use of balanced compounded feed is negligible and health care is mainly dependent on traditional medicines and ultimately, fate of the animals. However, as the investment level and out-of pocket expenses are almost negligible, farmers continue to rear livestock. Poor infrastructural facilities for delivery of livestock support services is another serious constraint. The small size of landholding with low production potential also limits the scope for growing green fodder on agricultural holdings. Hence, the animals depend on common property resources which are not systematically managed and the quality of feed and fodder from common lands is also inferior. Livestock rearing can become an economic enterprise if development initiatives strengthen the entire value chain and the activity is self-sustainable. Farmers can be motivated to adopt technically sound and economically viable improved livestock farming practices only if they are assured of goat markets and quality input services. Follow up on supervision, monitoring, a system of performance-linked incentives and accountability is critical for the success of any development initiative in Jharkhand. The livestock improvement programme in Jharkhand should focus on indigenous cattle, goat, pigs and poultry. The rural poor require a selective cattle breed improvement programme which can serve their requirement for draught animal power and increase the milk yield. In the periurban areas and among the resource-rich farmers, crossbred animals can become instruments of dairy development. Goat rearing needs to be promoted to provide meat and milk. Investment initiatives can also be taken up for promoting small-scale enterprises in rural areas to process the livestock produce. Based on the incidence of poverty, geographical representation of the state and demographic characteristics, the study suggests targetting a few districts for livestock development in the first phase.